Dietary exclusion of fructose and lactose after positive breath tests improved rapid‐transit constipation in children. Issue 6 (14th August 2018) - Waingankar, Kasturi; Lai, Christoper; Punwani, Vishal; Wong, Jeremy; Hutson, John M; Southwell, Bridget R
Abstract : Aims: Exclusion of f ermentable o ligosaccharides, d isaccharides, m onosaccharides, and p olyols (FODMAPs) from the diet is effective in alleviating symptoms of irritable bowel syndrome (IBS) in adults. Rapid‐transit constipation (RTC) is a recently discovered subset of chronic constipation and has been linked to food intolerance. The aim of this study was to audit the effect of specific FODMAP elimination diets in children with RTC. Methods: This was an audit of children presenting to a tertiary children's hospital surgeon with refractory chronic constipation who had rapid transit in the proximal colon on nuclear imaging; had hydrogen/methane breath tests for fructose, lactose, and/or sorbitol intolerance; and were advised to exclude positive sugar under clinical supervision. Patients filled in a questionnaire rating severity of constipation, abdominal pain, and pain on defecation with a visual analogue scale (VAS, 0 = none, 10 = high) and stool consistency for 6 months before and after dietary exclusion. Results: In responses from 29 children (5–15 years, 21 males), 70% eliminated fructose, and 40% eliminated lactose. There was a significant reduction in the severity of constipation (VAS mean ± SEM, pre 5.8 ± 0.5 vs post 3.3 ± 0.6, P < 0.0001), abdominal pain (5.1 ± 0.6 vs 2.8 ± 0.5, P = 0.0004), pain on defecation (5.8 ± 0.6 vs 2.6 ± 0.5, P < 0.0001), and increase in stool wetness (Bristol Stool Scale pre 3.3 ± 0.3 vs post 3.9 ± 0.2, P = 0.004). Conclusion: Children with RTC showed significant improvements in constipation and pain after excluding the sugar indicated by positive breath tests, suggesting that specific sugar‐exclusion diets may have a role in the management of RTC in children. Abstract : Rapid transit constipation (RTC) is a new subset of constipation and requires distinct treatment from slow‐transit constipation. Exclusion of specific FODMAP sugars significantly improved the severity of constipation, reduced abdominal pain, pain on defecation, straining, anal tears, blood in stool, stool consistency and decreased laxative use in children with RTC. The results of this study suggest that specific FODMAP sugar exclusion diets have a promising role to play in the management of RTC in children.